Active RFID-based Indoor Positioning System (IPS) for Industrial Environment - Abdul Alif Wafi, Ab Razak; Fahmi, Samsuri (2015)
This paper propose an active RFID-based indoor positioning system (IPS) for industrial environment. The system is quite similar to Global positioning system (GPS). However GPS can only work if the device is directed to the satellite. This work are to overcome the weakness of GPS capability for tracking an objects that did not receive a satellite signal. The methods, technique and technology of tracking system also been discussed in this paper. However, the work mostly focus on Received Signal Strength Indicator (RSSI) technique. Each technique are have their own deficiency. Several step are done to overcome those deficiency. Super High Frequency (SHF) RFID are used in this development of IPS.